Ideational Aspect of Systemic Functional Grammar in Bush's and Al-Assad's First Inaugural Speech - Sameer, Imad Hayif; Al Dilaimy, Hazim Hakkush (International Journal of Psychosocial Rehabilitation, 2020)
Depending on political discourse, the politicians try to win the favorite response from the audience. For this reason, the theory of critical discourse analysis (CDA) which is used to analyze political discourse forms the base for analyzing the data (Bush's and Al-Assad's first inaugural speeches). Systematic Functional Linguistics is used as an approach of CDA to analyze the data focusing on the point of transitivity which enables readers to know the way by which language serves to achieve specific ideologies and power. This paper aims at clarifying the experiential or ideational metafunction in which language is studied from the perspective of how it is used to talk about events, states and entities in the world, to interpret or construe the speaker's view of the world. The participants of any conversation use cognitive categories of this metafunction which are reflected by the six main types of specific processes which are: Material (processes of action), Mental (processes of sensing which clarify or construe our interior world), Relational (process of being and having), Verbal (processes of conveying messages, by saying, and so on.), Behavioral (human physiological processes) and Existential (processes of existing). This article hypothesizes that Material processes and Relational processes have an advanced order in the sample in question. Data analysis and conclusion prove and support these two hypotheses.